The Point Is to Change It: An Ode to Sam Porter's ‘Why Nurses Should be Marxists’ or, Why Nursing Must be Radical - Dillard-Wright, Jess (Nursing philosophy, 2026)
This is a tribute to Sam Porter's 2019 paper, ‘Why Nurses Should be Marxists’ in honour of the 25th anniversary of the journal Nursing Philosophy. In that paper, Porter made the case that nurses should be Marxist. While Porter was clear that Marxism could not solve all of nursing's problems, he made the case that it was an important start. I thought I would take up Porter's call to Marxism, to engage with it seriously, to offer up some extensions, to call folks to action. With this paper, in homage to Porter and also all the dreamers, movers, actors, organisers, and carers, I want to offer up the imperative to speak and act up in the face of rising authoritarianism and its threats to health, wellbeing, and liberation for us all. I get there by first outlining Porter's (2019), argument about why nurses should be Marxists. I then add the prefigurative potentials of anarchism as a praxis for nursing. From here, I go on to make the case that, whether communist or anarchist or abolitionist, nursing must be radical should we wish to survive our fascist present. After outlining the current order of things, I move to thinking about what might be possible, a speculative exercise in dreaming pushing off from current events. Possibility gives way to making things different, some provisional moves to build the futures we dream of in the face of perilous presents.